Optimization of Low-Carbon Footprint Quaternary and Quinary (37% Fly Ash) Cementitious Nanocomposites with Polycarboxylate or Aqueous Nanosilica Particles - Styliani Papatzani; Kevin Paine (Advances in Materials Science and Engineering)
The dispersion medium of nano-SiO2 (nS) particles can have a significant effect on the properties of nanoparticles themselves and consequently on the cement binders it will be added to. In this paper, nS particles dispersed in (a) polycarboxylate or (b) water were added to a low-carbon footprint reference binder containing 43% Portland cement (PC), 20% limestone powder (LS), and 37% fly ash (FA) by mass of binder. Eight quaternary binders containing nS, PC, LS, and FA and eight quinary binders comprising nS, PC, LS, FA, and silica fume (μS) were investigated. nS was added at 0.1%, 0.2%, 0.5%, or 1.0% by mass of binder as a replacement of LS for the quaternary binders and at 0.5% or 1.0% for the quinary binders. The nanoparticles were examined via transmission and X-ray scanning electron microscopy (TEM/SEM/EDX). For the pastes, compressive strength tests and thermal gravimetric analyses (TGAs) were performed at days 1, 7, 28, and 56, all testified to additional pozzolanic activity and additional C–S–H production. X-ray diffraction analyses and backscattered scanning electron imaging carried out on specific formulations also confirmed this finding at days 1, 28, and 56. Notwithstanding the additional pozzolanic reactivity, nS particles could not mitigate the delayed hydration of the reference paste in the early ages. In such complex formulations, the hydration products seem to create a wrapping around the FA particles delaying their activation at early ages. At later ages, the 0.5% nS addition provided strength, microstructural, and hydration improvements. The polycarboxylate/nS particles provided more pronounced strength improvements at 0.5% addition, possibly due to their superplasticizing effect. Lastly, a tabulated literature review on the thermal decomposition ranges of the hydration products of cementitious nanocomposites is also presented.